Penggunaan Aplikasi Animaker pada Mata Pelajaran Pendidikan Agama Islam Kelas III SD Negeri 07 Sintuk Toboh Gadang - Citra, Yulia (Darul Yasin Al Sys, 2023)
Media is something that cannot be separated from a learning process. When using media, there needs to be variety so that students do not get bored. This research aims to prove that using Animaker media as a medium in learning can produce animated video works that are easy to understand and interesting for students and can be used as teaching materials that are effective for use in the learning process. This research is a quasi-experiment (one group pretest-posttest design). The main instrument in the researcher's own research was carried out to test the validity and effectiveness of the learning videos used, validity trials were carried out using questionnaires, questionnaires were given to respondents and then analyzed by the researcher, as well as the results of student tests which were carried out using pretest and posttest then The participants' pretest and posttest results were taught for analysis by the researcher in tabular form. The subjects of this research were class III students at SDN 07 Sntuk Toboh Gadang, totaling 20 students. Based on the results of data analysis, the results obtained were 1) the average score from the pretest test results with a percentage of 59.6% which was included in the